THE EFFECT OF INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE ON FIRM VALUE WITH RETURN ON INVESTMENT AS A MODELING VARIABLE IN THE MINING INDUSTRY LISTED ON INDONESIA STOCK EXCHANGE - Rangkuti, Maryam Monika (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to analyse the effect of intellectual capital, profitability, leverage, firm size and firm growth on firm value with Return On Investment as a moderating variable in Mining Sub Sector Companies listed on the Indonesia Stock Exchange Period 2013-2017. The study was conducted on 29 mining companies listed on the IDX. Data analysis techniques used in this study are Multiple Regression analysis and Moderating Regression Analysis with the help of the E-Views program. The results of the study simultaneously showed a significant influence between intellectual capital profitability, leverage, firm size and firm growth on firm value. Partial testing shows that intellectual capital and firm growth does not affect firm value while profitability and leverage have a positive and significant effect on firm value. Firm size has a negative and significant effect on firm value. Return on investment has no significant effect in mediating the relationship between intellectual capital and firm value.